Effects of biosolids application on soil chemical pr ope rtie ties in peri-urban agricultural systems - Khai, Nguyen Manh; Ha, Pham Quang; Vinh, Nguyen Cong; Gustafsson, Jon Petter; Oborn, Ingrid (VNU Journal of Science: Earth and Environmental Sciences; Vol 24 No 4, 2008)
Abstract